Redefining a University Library’s Reference Service in 2018: A Continuum of Service - Fournier, Karine (Université d'Ottawa | University of Ottawa, 2019)
The University of Ottawa Health Sciences Library (HSL) has completely redefined its services to users over the past three years to better reflect the changing needs of library users, such as preference for digital over print, and increasing needs for teaching and research support. This presentation will provide an overview of HSL initiatives through: 1) The merger of the circulation and reference services This fusion of services meant a redistribution of employees’ tasks, where librarians withdrew from the reference desk and where support staff increased their knowledge of the reference service through several training sessions. This uptraining enabled employees to offer a basic reference services to users and allowed them to better allocate (triage) appropriate user requests. 2) The development of an individualized research consultation service Individualized consultations are tailored appointments for health sciences and medicine students and researchers offered by librarians, in order to provide in-depth assistance for their research projects, large or small. 3) The development of a triage service for consultations This triage service was intended to meet different needs: help a colleague with a temporary request overload, or to take care of requests directly from the service point referred by support staffs. The objective of these different services is to help our users based on a continuum of service, that is, from simple to complex requests, and this, in a completely fluid and transparent manner for library users. Learning objectives: -Participants will gain applied knowledge on how to change their service model, with tips on how to best overcome obstacles. -Participants will learn how to best use certain tools, such as LibCal, to create a seamless service to their users.
Keywords: reference service; Academic Library; Health Sciences Library; One-service desk; individualized research consultations